Impact of Lifestyle Modification Module on Adherence to Therapeutic Regimen of Children and Adolescents with Beta Thalassemia Major (Medico Legal Update, 2021)
Healthy lifestyle behaviors are important for thalassemic children and adolescents to prevent disease-relatedcomplications and improve quality of life. This study aimed to evaluate the effect of lifestyle modificationmodule on adherence of children and adolescent suffering from beta-thalassemia major. Design: A quasiexperimental design was utilized to conduct the study. Sampling: A purposive sample comprised of 80children & adolescents with beta thalassemia major. Tools: I-Interviewing questionnaire, II-Childrenadherence tools: It was used to assess children and adolescents’ adherence with: (a) Medication (Morisky),(b) Therapeutic regimen (diet, physical exercise, and follow up). (c) Levels of perceived stress, (d) Sleepquality domains and developed intervention lifestyle modifications module.Results: This study revealed that more than three quarter had satisfactory knowledge about ß-TM postlifestyle modification module implementation and the majority of children and adolescents with ß-TM wereadherent to taking medicines yesterday post module implementation.Conclusion: There were significant improvements of knowledge and adherence of the studied children andadolescents with ß-TM to therapeutic regimen post the lifestyle modification module application and therewere positive correlations between all variables of the studied children and adolescents with ß-TM.